Producing and consuming China's new urban space: State, market and society. (November 2015) - He, Shenjing; Lin, George CS
The extant literature on urban China is preoccupied by concerns over the production and usage/consumption of urban space in relation to the dualistic state–market or state–society relation. This special issue presents a collection of carefully selected papers to counter-balance the skewed tendency observed in current urban China studies. We argue that the growth and spatiality of China's new urbanism can be better understood by a critical analysis of how the state, market, and society interact in the processes of producing and consuming urban spaces in a rapidly changing global and local context. We propose that contemporary Chinese urban processes and experiences can be demonstrated holistically and realistically by placing due attention on both the production and consumption of China's new urban spaces and the resulting contestations and contradictions. Our collective effort to examine how China's state–market–society triad plays out in the production and consumption of urban spaces has yielded significant insights to advance ongoing enquiry in urbanising China in response to the advocacy for a decentring theorisation of the urban revolutions taking a perspective inclusive of the voices from the global south.